Assessment of Flood Damaged Infrastructures in Bosnia & Herzegovina and Serbia: An SEG Geoscientists without Borders Project - Komatina, S.; Suto, K.; Urosevic, Milovan (2015)
A heavy rainfall in the Balkan area caused a lot of damage to the infrastructure by floods and landslides in the catchment area of the Sava River. Geoscientists without Borders took up the proposal by an international team of volunteers to assist the recovery effort in the states of Bosnia & Herzegovina and Serbia by providing geophysical surveys and training. This paper presents an outline of the projects.